Efficacy and safety outcomes of PD-1/PD-L1 inhibitors in recurrent cholangiocarcinoma: a real-world, multicenter and retrospective study - Lihui Lin; Yansong Lin; Wei Chen; Xia Yang; Xianwen Guo; Yanqin Wu; Xiaoyu Yin; Zhen Ding; Jingping Yun (BMC Cancer)
Abstract Background The recurrence rate of cholangiocarcinoma (CCA) is high, and there are currently no evidence-based treatments for recurrent CCA. This study aimed to evaluate the effectiveness and safety of programmed cell death protein-1 (PD-1) and programmed cell death ligand-1 (PD-L1) inhibitors in patients with recurrent CCA. Methods Patients diagnosed with recurrent CCA and treated with PD-1/PD-L1 inhibitors between January 2019 and June 2024 were retrospectively enrolled and analyzed. Overall survival (OS), progression-free survival (PFS), and tumor responses were evaluated, and immunotherapy-related adverse events were recorded. Cox regression analyses were conducted to assess prognostic factors associated with the efficacy of PD-1/PD-L1 inhibitors in recurrent CCA. Results A total of 140 recurrent CCA patients were enrolled for analysis. The median follow-up time of the cohort was 16.7 months, the median OS and median PFS were 32.5 months and 9.5 months, respectively. The 6-month, 1-year and 2-year OS rates were 93.7%, 76.3% and 57.5%, respectively. The 6-month and 1-year PFS rates were 71.5% and 42.1%, respectively. The objective response rate and disease control rate were 30.0% and 66.4%, respectively. Recurrence interval, immunotherapy cycles, and immunotherapy responder were associated with OS and PFS. In addition, carcinoembryonic antigen and Eastern Cooperative Oncology Group performance status score independently served as prognostic factors for OS. The most common adverse events were anemia, leukopenia, fatigue, elevated AST, neutropenia, hypoalbuminemia. There were no treatment-related deaths reported in this study. Conclusion PD-1/PD-L1 inhibitors therapy offers a promising option for recurrent CCA.